Entity Framework 4.1: expert's cookbook : more than 40 recipes for successfully mixing test driven development, architecture, and Entity Framework code first - Liles, Devlin (Packt Pub./Enterprise, 2012)
This book takes a step-by-step problem solving approach that leads you through a problem and explains each step in detail to accomplish the goal. This books gives you concrete code examples as well as detailed information on the decisions involved. This book is for intermediate to advanced .NET developers who have used LINQ to SQL or Entity Framework in some form but want to have more control over the implementation.
Keywords: Microsoft .NET Framework.; Microsoft .NET Framework; Application software -- Development.; elektronické knihy; electronic books